Pelatihan Bahasa Pemograman Python Berbasis Modul Sympy Untuk Memvisualisasi Konsep Fisika Matematika Bagi Mahasiswa Calon Guru - I Wayan Sudiarta; Lalu Rudyat Telly Savalas; Thufail Mujaddid Al-Qoyim; Putri Julia Maemum; Mega Safana; Ahmad Fadli; Nurjamilah; Muhamad Hendri Diarta; Chorina Ika Ristanti; Nanda Nabila Maharani; Siti Nurkhaliza; Ulfa Dwiyanti; Jannatin Ardhuha; Ap’aluddin (Universitas Mataram, 2021)
Basic programming skills are perceived to be increasingly important in this rapidly changing era. Mastery of programming languages is not only important for informatics and computer technology activists, but also becomes essential for science, science education, and pre-service science teachers. To deal with this matter, an outreach program has been carried out in by undertaking python language training with sympy module for prospective science teachers. The activity aims to give training to student teacher to have basic knowledge in python programming by using sympy module, to gain a deeper skill to visualize physical mathematics concepts and utilize the absorbed skills in mastering other physics concepts. The training includes introduction to python language, python-jupyter and sympy installation, script and module usage, introduction to google collab and application python-based sympy module to visualize concepts in physical mathematics. The two days training activities received good response from participants. A total of 95.5% of participants rated the training material as highly relevant and in line with expectations of participating in the training. In addition, the discussion and Q&A activities at the end of the activity also help participants to understand the material better. Students particularly learnt to solve problems in physical mathematics easily and quickly when using python-based programs sympy module. From the series of activities that have been carried out, it can be concluded that this outreach activity showed an obvious benefit for science student teachers, and hence it is advisable to do similar activities with broader participants in the future.